What does 'First' Mean in Mark 9,11? - Flowers, Michael V. (Ephemerides theologicae Lovanienses, 2021)
Traditionally, the word 'first' in Mark 9,11 has been taken to mean, 'prior to the Messiah'. But recent commentators understand it to mean, 'prior to the resurrection', 'the day of Yhwh', or 'the restoration of all things'. The traditional interpretation is indirectly supported by the inherent weaknesses of these alternative interpretations. It is positively supported by considerations of form-, redaction-, and text-criticism, as well as evidence from within Mark’s Gospel and other traditions of the early Jesus movement and wider Judaism which envisages John or Elijah as a messianic forerunner. The traditional interpretation also coheres with the Transfiguration and early apologetic interests of Jesus’ followers.